2003
DOI: 10.1203/01.pdr.0000049517.47493.e9
|View full text |Cite
|
Sign up to set email alerts
|

Learning, Memory, and Transcription Factors

Abstract: The following article is the second in this series. It reviews genes and metabolic pathways involved in learning and memory in lower animals and in humans. These new, exciting studies will contribute to greater understanding of the molecular abnormalities responsible for cognitive disorders in children. Cognitive disorders in children have traditionally been described in terms of clinical phenotypes or syndromes, chromosomal lesions, metabolic disorders, or neuropathology. Relatively little is known about how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 51 publications
(58 reference statements)
1
19
0
Order By: Relevance
“…Decreased brain volume in CLS is likely to stem from disruption of core RSK2 protein functions associated with mutations of this gene. The RSK2 protein activates the transcription factor cyclic AMP response element binding protein (CREB) [17,18], which in turn, regulates neuronal survival factors and is required for axonal growth, neuro-protection, and synaptic plasticity associated with long-term memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased brain volume in CLS is likely to stem from disruption of core RSK2 protein functions associated with mutations of this gene. The RSK2 protein activates the transcription factor cyclic AMP response element binding protein (CREB) [17,18], which in turn, regulates neuronal survival factors and is required for axonal growth, neuro-protection, and synaptic plasticity associated with long-term memory.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent neuronal stimulation activates a cascade of molecular components that results in transcription and translation of new proteins, which strengthen and increase the number of synapses [18,22]. The RSK2 protein is directly involved in these signaling pathways [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired plasticity refers to situations in which genetic or acquired disorders disrupt molecular plasticity pathways, for example in genetic and acquired disorders such as TBI that cause cognitive impairment [46]. The Snoezelen environment may be an enriched environment that is beneficial for children with disruption in the signalling cascades that have been shown to mediate learning, memory and other forms of neuronal plasticity in animal models [47,48]. It has been reported that children who have severe or moderate mental retardation may find their immediate environment chaotic, frightening, confusing and unstimulating [46].…”
Section: Discussionmentioning
confidence: 99%
“…The common theme for these disorders is that they disrupt specific steps in the pathways that lead to changes in numbers of synapses or in the strength of synapses based on synaptic activity (24). For example, neurofibromatosis type 1 (NF-1) is caused by a mutation in the tumor suppressor gene for the protein neurofibromin, which is a GTPase activating protein (GAP) (25).…”
Section: Abnormal Plasticity In Pediatric Brain Disordersmentioning
confidence: 99%